10.24843 A Geography Dialect Of Wakatobi Language In Southeast Sulawesi - Taembo, Maulid; Dhanawaty, Ni Made; Mbete, Aron Meko; Putra, Anak Agung Putu (e-Journal of Linguistics; Vol 12 No 2 (2018): eJL-JulyDO - 10.24843/eJL.2018.v12.i02.p.03, 2018)
The problems on Wakatobi language variations and there is not any completed dialectology study of Wakatobi which is relevant and beneficial to conduct this study. This study aims at (1) describing and analyzing the phonology and sound change of Wakatobi; and (2) analyzing the group of Wakatobi based on dialectometry. This study uses generative dialectology to analyze the phonological aspect, and traditional dialectology to analyze the lexical aspect. The primary data is obtained through interviewing method in 25 villages as observation point in Wakatobi regency, and document study as secondary data. In analyzing the data, this study uses apportion and equal methods, and dialectometry method.             Wakatobi language has five vowels, namely /i, a, ?, ?, u/; and 32 consonant phonemes, they are /b/, /?/, /p/, /d/, /?/, /t/, /g/, /?/, /k/, /j/, /?/, /?/, /ñ/, /m/, /n/, /s/, /h/, /l/, /r/, /?/, /c/ /y/, / m b/, / m p/, / n d/, / n t/, / n s/, / ? g/, / ? k/, / n c/, / n j/, and /?/. There are two kinds of phonological processes of Wakatobi language discussed in this paper, namely assimilation and the structure of syllable. The assimilation process of Wakatobi occurs mostly on vowels, particularly for vowel harmony. Besides, it includes progressive and regressive assimilations. Further, Wakatobi can be grouped into six subdialects, they are (1) Waha, (2) Kapota, (3) Mandati-Lia, (4) Kaledupa, (5) Tomia, and (6) Binongko. The names of subdialect come from the names of small islands of Wakatobi and Wakatobi community.